Mapeamento de ontologias empresariais para modelos de processos de negócio em BPMN, com aplicação em processos de software - Stuchi, Renan Bergamin [UNESP] (2015)
The main goal of this work is to present a methodology to map enterprise ontologies in graphical models of business processes, with the graphical notation Business Process Model and Notation (BPMN). The intention is to obtain a graphical structure that contributes to the ontology understanding, including the relation between processes and the collaboration network among the actors involved. The mapping process proposed is partly automated and is based on the principle that the ontology is able to be converted into a Resource Description Framework - RDF - 1.1 structure. So, it was defined a tagging process to the ontology in RDF, which allows the automatic mapping to XPDL 2.2 language (XML Process Definition Language) through a software tool (parser), denominated RDFtoXPDL. For the development of this tool, it was used the SPARQL language to query data in the tagged RDF file. The resulted file in XPDL can be imported by modeling process systems, in a way that allows the viewing and the use of the diagrams in BPMN. This work also presents an application of the proposed methodology to an enterprise ontology of the MPS Reference Model for Software (RM-MPS-SW), considering the levels G and F. The representation in BPMN of the RM-MPS-SW can support the implementation of this model in organizations of software development, stimulating the adoption of the future Business Process Management (BPM) approaching